PC Based Real Time Control of DC Motor - Mohamad Fauzi Radsanjani; Dwi Astharini (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2018)
Abstract – This final project report present a Pc based real time control of DC motor. Real time control systems can be defined as a technology which is related to mechanical application, electronic, and computer-based systems. In general, the equipment that is often used for controlling speed system is Arduino Mega 2560, DC motor, motor driver IC L298N, speed sensor IC LM393, and voltage sensor. Software in the system I used Matlab Simulink to monitor and control the speed of dc motor will show real data, they are displayed in signal RPM and signal Voltage, Matlab Simulink is used program to let the operator operates the system well. This monitor and control system can improve the effectiveness and efficiency in various industrial fields. Keyword – PC, Real Time, Control, DC Motor